Бурджане (булг-р) Степного Подонцовья в составе Хазарии - Красильников, К.И. (Степи Европы в эпоху средневековья, 2009)
Alans (al-lan) and proto-Bulgarians (burgean) formed an ethnic nucleus of population of the western outskirts of Khazaria which became its part in the middle of the 7th century as a result of wars. The Kaganat administration took a dual attitude towards their nationals determined both by military strategies and economic interests.